2022
DOI: 10.3390/pathogens11030367
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pythium oligandrum in the Biological Control of Roundworm Infection in Dogs and Cats

Abstract: Pythium oligandrum is an oomycete used in veterinary medicine to treat dermatophytosis in animals. The ovicidal potential against various types of parasite eggs has not been investigated. Ascarids are very common in young animals and the resistance of eggs in the external environment is very high. A commercial product containing P. oligandrum was used in the present study. Its ovicidal action against Toxocara spp. eggs was investigated. Thus, two categories of media (soil and sandstone) were used, on which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Previously, a commercial preparation of P. oligandrum called Ecosin was shown to have larvicidal activity towards the nematode Uncinaria stenocephala, which parasitizes animals [58]. The P. oligandrum preparation Ecosin can also control the roundworm infection in dogs and cats caused by the ascarid nematodes Toxocara canis and T. cati [8]. The mechanisms by which Ecosin works here with these nematodes appear to involve nematophagous activities towards eggs and larvae after the germination of P. oligandrum from the spores contained in the Ecosin preparation [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a commercial preparation of P. oligandrum called Ecosin was shown to have larvicidal activity towards the nematode Uncinaria stenocephala, which parasitizes animals [58]. The P. oligandrum preparation Ecosin can also control the roundworm infection in dogs and cats caused by the ascarid nematodes Toxocara canis and T. cati [8]. The mechanisms by which Ecosin works here with these nematodes appear to involve nematophagous activities towards eggs and larvae after the germination of P. oligandrum from the spores contained in the Ecosin preparation [8].…”
Section: Discussionmentioning
confidence: 99%
“…P. oligandrum can also promote plant growth, which involves the production, by P. oligandrum, of the auxin compound tryptamine [7]. Recently, there has been a report of a P. oligandrum preparation called Ecosin controlling a parasitic disease in dogs and cats caused by the ascarid nematodes Toxocara canis and T. cati [8]. To our knowledge, however, there are no reports of P. oligandrum having nematicidal activity towards plant parasitic nematodes or controlling nematode-caused plant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Fonseca et al, with a formulation with fungus Pochonia chlamydosporia, concluded that the rapid transition from egg to larvae stage was not affected by fungus Pochonia chlamydosporia; therefore, the fungal formulation containing Pochonia chlamydosporia was not efficient in the biological control of bovine gastrointestinal nematodes [3]. The results of Luca et al indicated an ovicidal action of Pythium oligandrum, supporting the prospects of its use in the decontamination methods of various surfaces or environments where ascarid eggs from carnivores are found [4]. Diagnostic.…”
mentioning
confidence: 98%